A network analysis of the causal attributions for obesity in children and adolescents and their parents. Issue 9 (21st October 2019) - Brogan, Amy; Hevey, David; Wilson, Charlotte; Brinkley, Aoife; O'Malley, Grace; Murphy, Sinéad
ABSTRACT: Illness attributions inform how people understand illness and relate to psychological outcomes. Parental attributions may impact children's adjustment to illness. This study investigated child, adolescent and parental causal attributions in paediatric obesity and illustrates the relationships between these attributions using network analysis. A cross-sectional design using the diagram network analytic method. Thirty children and 25 parents generated individual causal attribution maps. Network theory was used to analyse causal effects and results were visualised using network models. The results indicated large individual variation in the networks. Activity and eating-related variables featured strongly in child and parent networks. Children viewed their activity while parents regarded their child's eating behaviours as the main drivers of obesity. The characterisation of some children along an internalising dimension was supported in both networks. Habitual cluster behaviours and difficulties in regulation were identified in the child network. Parents ascribed significance to the future impact of obesity on body image and mood. Challenges in parent management were also indicated. Obesity is a heterogeneous condition, requiring a tailored treatment approach. Therapeutic directions were identified in the areas of activity, food intake, sleep hygiene and parent management. Attributional processes represent a potential mechanism to tailor obesity treatment. Further research is needed to establish the relationship between attributions, treatment engagement and outcome.